MENINGKATKAN PEMAHAMAN MACHINE LEARNING DI KALANGAN SISWA SMA: TANTANGAN DAN SOLUSI - Fat, Joni; Tyven Christopher Gilbert; Julius Sembiring (Jurnal Bakti Masyarakat Indonesia, 2025)
In the era of the Fourth Industrial Revolution, technology and information education have become essential aspects of the high school curriculum. Machine Learning (ML), as one of the key technologies, plays a role in developing critical and analytical thinking skills essential for students’ futures. However, Santa Theresia High School faces challenges in teaching ML, including limited resources for practice, teacher competence, and students’ perception of ML as a difficult and abstract subject. This activity was designed as a Community Service initiative to introduce ML to students through interactive and practical methods. The event took place on March 6, 2024, at Santa Theresia High School, beginning with a theoretical session on the fundamentals of ML led by Dr. Joni Fat. Students were introduced to ML applications in everyday life and proceeded with hands-on practice using RapidMiner and Weka software. In this session, students learned to perform simple modeling tasks, such as data classification and clustering, through approaches that resemble real-life situations. The results of the activity showed an improvement in students’ understanding of ML concepts, as evidenced by their ability to complete practical tasks independently and their high interest in this technology. Group discussions at the end of the activity deepened students’ understanding through reflections on their learning experiences, identifying both the potential and challenges of using ML. Based on the evaluation results, this activity successfully increased students' interest and confidence in ML, with 85% of students feeling they understood the basics of ML better and 78% expressing interest in further studying this technology. Other positive impacts included improved collaboration skills through group discussions and simulations. Challenges encountered included infrastructure limitations and the need for further teacher training. The results of this activity are expected to enhance the quality of technology teaching at Santa Theresia High School, preparing students to face technological challenges in the future. ABSTRAK Di era Revolusi Industri 4.0, pendidikan teknologi dan informasi menjadi aspek penting dalam kurikulum Sekolah Menengah Atas (SMA). Machine Learning (ML), sebagai salah satu teknologi utama, berperan dalam mengembangkan keterampilan berpikir kritis dan analitis yang esensial bagi masa depan siswa. Namun, SMA Santa Theresia menghadapi tantangan dalam pengajaran ML, termasuk keterbatasan sumber daya praktik dan kompetensi guru, serta anggapan siswa bahwa ML adalah materi yang sulit dan abstrak. Kegiatan ini dirancang sebagai upaya Pengabdian kepada Masyarakat untuk memperkenalkan ML kepada siswa dengan metode yang interaktif dan aplikatif. Pelaksanaan kegiatan berlangsung pada 6 Maret 2024 di SMA Santa Theresia, dimulai dengan sesi teoretis tentang dasar-dasar ML yang dipimpin oleh Dr. Joni Fat. Siswa diperkenalkan dengan aplikasi ML dalam kehidupan sehari-hari dan dilanjutkan dengan praktik menggunakan perangkat lunak RapidMiner dan Weka. Dalam sesi ini, siswa belajar melakukan pemodelan sederhana, seperti klasifikasi dan pengelompokan data, melalui pendekatan yang mendekati situasi sehari-hari. Hasil kegiatan menunjukkan peningkatan pemahaman siswa terhadap konsep ML, terbukti dari kemampuan siswa menyelesaikan tugas praktis secara mandiri serta tingginya minat mereka terhadap teknologi ini. Diskusi kelompok pada akhir kegiatan memperdalam pemahaman siswa melalui refleksi pengalaman belajar, mengidentifikasi potensi serta tantangan dalam penggunaan ML. Berdasarkan hasil evaluasi, kegiatan ini berhasil meningkatkan minat dan kepercayaan diri siswa terhadap ML, dengan 85% siswa merasa lebih memahami dasar-dasar ML dan 78% tertarik untuk mempelajari teknologi ini lebih lanjut. Dampak positif lainnya adalah peningkatan keterampilan kolaborasi melalui diskusi dan simulasi kelompok. Tantangan yang dihadapi meliputi keterbatasan infrastruktur dan perlunya pelatihan lanjutan bagi guru. Hasil kegiatan ini diharapkan dapat meningkatkan kualitas pengajaran teknologi di SMA Santa Theresia, mempersiapkan siswa menghadapi tantangan teknologi di masa depan.